The Meaningful Role of Affection in Education: The Emotional Perspective in Pedagogy - Nilna Azizatus Shofiyyah; Tedy Sutandy Komarudin; Dewi Rika Juita (Universitas Pahlawan Tuanku Tambusai, 2023)
This study explores the significance of love within the realm of education and examines the utilization of an emotional approach in the teaching and learning process. This research aims to comprehend the importance of love in education and explore the practical application of the emotional approach to enhance learning outcomes. Through an extensive review of existing literature, this study highlights the factors that influence the successful implementation of the emotional approach and its implications for improving teacher-student relationships and fostering student motivation. The findings of this research provide valuable insights for educators and educational practitioners seeking to understand the role of love in education and the practical integration of the emotional approach. Keywords: Love, education, emotional approach, significance, learning motivation